Ragnarøk: An Elegy. (2nd January 2016) - Adams, Michael
Abstract : In a world where names of cosmic significance are daily degraded to the level of mere lexis, Ragnarøk long remained above the fray. Now, it too has lost its onomastic grandeur as meaning 'the fall of the gods and civilization after an all-inclusive battle between the Jætter and the Æsir' and has been brought down to mundane lexical use as 'really big mess' by a Danish detective novel and its English translation. Could the fall of Ragnarøk signal the Twilight of End of Times terminology? Will Gotterdamerung be the next mighty name to fall? All things — even our names for them — finally pass.